ANALISIS PENOKOHAN DAN NILAI PENDIDIKAN KARAKTER DALAM NOVEL ASMARANI KARYA SUPARTO BRATA DAN RELEVANSINYA SEBAGAI MATERI AJAR APRESIASI SASTRA JAWA DI SMA - Marsela, Dian; Waluyo, Budi; Sulaksono, Djoko (Universitas Sebelas Maret, 2017)
The objectives of this research are to describe: 1) Characterization in the novel Asmarani written by Suparto Brata; 2) character educational value that obtained from novel Asmarani written by Suparto Brata; 3) the relevance novel Asmarani written by Suparto Brata as Javanese literature appreciation learning material for Senior high school students. Method that use in this research is qualitative descriptive method. It obtained through analytical technique and informants interview. Data validity is obtained through sources triangulation and theories triangulation. Data sources of this research are documents and informants. Sampling technique of this research is purposive sampling. Research procedures are preparation stage, implementation stage, and finalization stage. Novel that analyzed in this research is novel entitled Asmarani written by suprapto brata. Researchers analyze the intrinsic value, namely; theme, plot, setting, point of view, messages of the story. However, the researcher is focused on the characterization and character educational value of the novel. Characterization analysis result shows that there are 6 genre of characters, those are; protagonist, antagonist, peripheral, central, complex, and simple character. Character explanation and its nature are analyzed through analytical and dramatic method. Asmarani contain many character educational values, such as religious value, honesty, tolerance, discipline, hard work, creativity, democraticity, curiosity, national spirit, homeland loving, achievement appreciation, friendship, peace, love to read, environment care, social care. In addition, novel asmarani is relevant as Javanese literature appreciation learning material for Senior high school students.